Pengembangan Bahan Ajar Berbasis Video Animasi Dengan Pendekatan Kontekstual Pada Materi Aritmatika Sosial Kelas VII SMP - Rusli; Said Fachry Assagaf; Selviana (Issues in Mathematics Education (IMED), 2023)
The purpose of this research is to develop and produce animated video-based teaching materials with a valid contextual approach. This research is a development research using a 4D model which consists of 4 stages, namely define, design, develop, and disseminate. This animated video teaching material was developed using the powtoon application. The subjects of this research were students of class VII 2 and class VIII 1. The data collected to answer the problem statement in the form of student responses and teacher responses. The research instrument used was a media expert and material expert validation questionnaire, a student response questionnaires and teachers response interview guide. The animation video products produced are 6 videos. The results showed that the animated video-based teaching materials were valid.